An Analysis Of Self-Efficacy, Welfare Status, And Occupational Choice Among Female Single Parents - Catherine J. Southwick; Bob Nolan (Adult Education Research Conference, 1998)
The concept of self-efficacy has been proposed as a possible explanation why women are deterred from pursuing higher paying, traditionally male occupations. This study sampled 199 women pursuing occupational training in Vocational-Technical Institutes to obtain some measure of occupational self-efficacy and compare those measures by non-traditional occupational training and welfare status.